Calculi removed from a woman, and a narwhal embryo - Mulder, Joseph, 1659 or 1660-; Ruysch, Frederik, 1638-1731 (1714)
Engraved by J. Mulder from a specimen by Frederik Ruysch. Calculi removed from women of various ages (fig. 1-4); in a specimen jar, the embryo of a narwhal (fig. 5). Title supplied by cataloger.